Comparison of Robot-assisted Enhanced-view Totally Extraperitoneal (eTEP) and Transabdominal Retromuscular (TARM aka TARUP) Ventral Hernia Mesh Repair: A Systematic Review and Meta-Analysis - Francesco Brucchi; Francesco Brucchi; Annabelle De Troyer; Richard Sassun; Richard Sassun; Gianlorenzo Dionigi; Gianlorenzo Dionigi; Filip Muysoms (Journal of Abdominal Wall Surgery, 2025)
BackgroundThis systematic review and meta-analysis compares robotic eTEP and TARM/TARUP in terms of complications, operative time, infections, length of stay, seroma, and short-term recurrence rates.MethodsA systematic review was conducted following PRISMA guidelines, searching MEDLINE, Embase, and CENTRAL until January 30, 2025. Studies comparing r-eTEP and r-TARM/TARUP in adults with ventral hernia were included. Primary outcomes were operative time and postoperative complications. Secondary outcomes included wound complications, length of stay, readmission, pain, and short-term recurrence. A random-effects model was used for meta-analysis, and study quality was assessed via the Methodological Index for Non-randomised Studies (MINORS) score.ResultsThree studies (308 patients: r-eTEP 176, r-TARM/TARUP 132) were included. Overall complications were lower with r-eTEP (RD: -0.17; 95% CI: -0.27 to −0.07; p = 0.001) and as was the case for minor complications (RD: -0.14; 95% CI: -0.22 to −0.06; p = 0.0008). No significant differences were found in major complications, SSI, recurrence, or 30-day readmission. Operative time was shorter with r-eTEP (MD: -25.66 min; 95% CI: -51.18 to −0.14; p = 0.05, I2 = 88%). Seroma formation was lower with r-eTEP (RD: -0.08; 95% CI: -0.15 to −0.02; p = 0.01). Length of stay was shorter with r-eTEP (MD: -2.64 days; 95% CI: -4.06 to −1.22; p = 0.004, I2 = 98%).ConclusionEvidence remains insufficient to favor one robotic approach over the other. High-quality prospective studies on patient outcomes and long-term recurrence are needed to guide surgical decision-making.Systematic Review RegistrationPROSPERO, identifier CRD420250650879.